Effect of lithium iodide on the performance of dye sensitized solar cells (DSSC) using poly(ethylene oxide) (PEO)/poly(vinyl alcohol) (PVA) based gel polymer electrolytes - Teo, Lay Lian; Tiong, T.S.; Buraidah, Mohd Hamdi; Arof, Abdul Kariem (Elsevier, 2018)
In this work, different concentrations of lithium iodide (LiI) have been added to the gel polymer electrolyte (GPE) containing PEO and PVA in equal ratio, tetrabutylammonium iodide (TBAI), ethylene carbonate (EC), dimethyl sulfoxide (DMSO) and iodine crystals (I2). The effect of introducing lithium iodide (LiI) into PEO-PVA blended GPE system having TBAI has been investigated in terms of optical, electrical, thermal and electrochemical characteristics. Fourier transform infrared (FTIR) spectroscopy has been carried out to study the interaction of LiI with the GPEs. The GPE without LiI showed the highest conductivity of 5.50 mS cm−1 at room temperature. With the incorporation of LiI, decrement in conductivity was observed. Dye-sensitized solar cells (DSSCs) with configuration FTO/TiO2/N3-dye/GPE/Pt/FTO have been fabricated and tested under white light of intensity 100 mW cm−2. The DSSC made of GPE with 1.34 wt% LiI exhibited highest efficiency, η of 6.26%.